Cognitive deficits in middle-aged and older adults with bipolar disorder and cognitive complaints: Comparison with mild cognitive impairment - Silva, Dina Lúcia Gomes da (2014)
Objective Cognitive impairment has been reported in elderly bipolar disorder (BD) patients, however, few studies have evaluated middle-aged and older BD patients using standardized cognitive assessments and none (to our knowledge) analysed middle-aged and older BD patients with recent cognitive complaints. The main objective of this study is to characterize the cognitive deficits of middle-aged and older patients with BD and compare them with the common agerelated cognitive deficits observed in Mild Cognitive Impairment (MCI). Methods For this retrospective study, a systematic search for all cases of BD patients submitted to a neuropsychological assessment from 1999–2007, at participant institutions, was performed, and cases were matched (1:2) by gender and age to a sample of MCI subjects. Results A total sample of 135 patients, 45 patients with the diagnosis of BD, clinically stable, mean age of 63.8 8.8 years, and 90 patients with the diagnosis of MCI, mean age of 64.2 8.4 years, was studied. Patients with MCI were more impaired in verbal memory, whereas BD patients showed more deficits in attention, motor initiative, calculation and verbal abstraction. Interestingly, discriminant analysis classified about half of the BD group as belonging to the MCI group. This BD subgroup showed deficits in episodic memory similar to MCI patients. Conclusions Patients with BD and patients with MCI have distinct profiles of cognitive impairment. A subgroup of BD patients with recent cognitive complaints may actually suffer from concomitant incipient MCI, and this finding may have diagnostic and therapeutical implications.